Esophageal Diameter on High-Resolution Computed Tomography – a Potential Useful Marker for Interstitial Lung Disease Severity in Patients with Systemic Sclerosis - Anja Ljilja Posavec; Lea Šalamon; Renata Huzjan Korunić; Nevenka Piskač Živković; Joško Mitrović (Acta Clinica Croatica)
Patients with systemic sclerosis (SSc) are at an increased risk of developing interstitial lung disease (ILD) and esophageal dysfunction, with frequently present esophageal dilatation. Our study aimed to investigate the relationship between esophageal diameter (ED) analyzed on high-resolution computed tomography (HRCT) with lung function tests and ILD evaluated with Warrick score. Thirty-nine patients with SSc were enrolled in this study. ED and Warrick score were evaluated by HRCT. The relationships between Warrick score, lung function, and ED were analyzed. Multivariate regression analysis was used to determine the effect of individual predictors on SSc-ILD. ILD was present in 25 (64%) patients. ED >10 mm in one or more of the measured locations on HRCT was present in 25 (64%) patients and 19 (76%) of these patients had concurrent ILD. Subjects with esophageal dilatation had a higher Warrick score and lower lung function tests. The measurement of ED was able to predict the presence of ILD in 69% of patients. Results suggest that evaluation of ED during regular HRCT follow-up could be useful in patients with SSc due to the association of esophageal dilatation with worse lung function tests and a more severe form of ILD.